Production of Agaricus blazei ss. Heinemann (A. brasiliensis) on different casing layers and environments - Zied, D. C. [UNESP]; Minhoni, M. T. A. [UNESP]; Kopytowski-Filho, J. [UNESP]; Andrade, Meire Cristina Nogueira de [UNESP] (Springer, 2010)
To investigate the yield and precocity of Agaricus blazei using to different casing layers and cultivation environments, five casing layers were prepared with soil (different textures), wood charcoal, and calcitic lime. After colonization, the composts were placed in two growing rooms (controlled environment and plastic greenhouse) and cased. The cycle was 120 days. Yield and precocity data were evaluated in a factorial combination (5 soil types x2 cultivation environments) and 8 replications. The results showed low yields when cultivated in a controlled room (1.55 kg of mushrooms per box) and yield values of different soils ranged between 1.61 and 1.88 kg of mushrooms per box. The precocity values of the different soils and environments ranged between 62 and 51% in the first 50 days of production. The various soil types did not differ statistically for yield values (kg) and the plastic greenhouse provided higher yields. The texture of the different soils and environment directly influenced precocity in A. blazei yield.
Keywords: Agaricus blazei; Medicinal mushroom; Casing layer; Cultivation environment; Yield